Recent Referees (Journal of Political Economy, 2021)
Previous articleNext article FreeRecent RefereesPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:Daniel AaronsonMartin AbelJerome AddaNikhil AgarwalMohammad AkbarpourRobert AkerlofIngvild AlmåsNabil Al-NajjarJoshua AngristOlof ÅslundEduardo AzevedoMartha BaileyMiguel BallesterDaniel BarronMarco BattagliniPatrick BayerMarianne BertrandTimothy BesleyManudeep BhullerNicolas BottanGiulia BrancaccioGreg BuchakLeonardo BursztynCharles CalomirisColin CamererOzan CandoganAndrew CaplinBharat ChandarGabe Chodorow-ReichGregory ClarkJulien CombeDiego CominAnna CostelloNatalie CoxDavid CutlerEduardo DavilaAlexandre de CornièreMonique De HaanEddie DekelMelissa DellEllora DerenoncourtManasi DeshpandeDouglas DiamondMichael DinersteinMatthias DoepkeChristian DustmannMatt ElliottHanming FangPeter FeldhutterPrice FishbackChristopher FlinnMarco FrancesconiAlexander FrankelPeter FredrikssonEric FrenchMarkus FroelichCary FrydmanJana GallusPeter GanongRobert GibbonsVincent GlodeUri GneezyMarion GousséDavid GreenMatthew GrennanFaruk GulPhilip HaileBarton HamiltonSamuel HartzmarkYinghua HeDavidson HeathBernard HerskovicFlorian HoffmannChristopher HousePeter HullJohn Eric HumphriesTullio JappelliMatthew JaremskiYuichiro KamadaLouis KaplowPinar Karaca-MandicKei KawaiMichael KeenScott KominersFabian KosseDorothea KüblerMarianna KudlyakAndreas LangeRenata LemosMoritz LenelKenneth LeonardArthur LewbelAnnie LiangLee LockwoodCorinne LowRalph LuettickeYao LuoMatteo MaggioriMihai ManeaYusufcan MasatliogluFabrizio MattesiniAlisdair McKayRobert McMillanMarc MelitzKonstantin MilbradtYuliyan MitkovJoshua MollnerJohn MondragonJoan MonrasJosé Montiel OleaThayer MorrillStephen MorrisAdair MorseJack MountjoyIsmael MourifiéXiaosheng MuJoseph MullinsKarthik NagarajanGaston NavarroChristopher NeilsonKevin NovanGuillermo OrdoñezJuan OrtnerMonica PaiellaJuan PantanoJonathan ParkerFernando ParroChristina PattersonPia PingerDevin PopeFranck PortierDavide ProserpioJohn QuahRicardo Quineche UribeValerie RameyNatalia RamondoPascual RestrepoAlbrecht RitschlSteven RivkinJames RobinsonGuillaume RocheteauKnut RøedEvan RoseEsteban Rossi-HansbergMarzena RostekJohn RustAldo RustichiniEvan SadlerRaffaella SadunYuval SalantBatchimeg SambalaibatHeather SarsonsMaximilian SchaeferRichard SchmalenseeBenjamin SchoeferChristoph SchottmuellerKarl SchurterFiona Scott MortonJoseph ShapiroMatthew ShapiroYotam Shem-TovAli ShouridehMichael SimkovicAndrey SimonovJeff SmithAlexandre SollaciRachel SoloveichikPaulo SomainiZheng SongIsaac SorkinPedro SouzaFrancesco SquintaniVictor StangoMatthias SutterMarco TabelliniSteven TadelisIna TanevaFelix TintelnotJean TiroleAlexander TorgovitskyKenneth TroskeBertil TungoddenSergio UrzúaJohn Van ReenenVictoria VanascoGreg VeramendiLise VesterlundAlessandra VoenaJonathan VogelFabian WaldingerChristopher WaltersMichael WeberJonathan WeinsteinDaniel WilhelmThomas WinberryChristian WolfGavin WrightBernard YeungAli YurukogluBasit ZafarGiulio ZanellaOren ZivUlf Zoelitz Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 129, Number 5May 2021 Article DOIhttps://doi.org/10.1086/715534 Views: 238 © 2021 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.